CHANGES IN VISUAL ACUITY AND MACULAR THICKNESS AFTER INTRAVITREAL BEVACIZUMAB IN VASCULAR RETINOPATHIES: Vascular Retinopathies - Islam, Qamar Ul; Dar, Asad Jamal; Hanif, Muhammad Kashif; Tarin, Sheraz; Tanvir, Amna (Pakistan Armed Forces Medical Journal, 2014)
Objective: To determine the effect of intravitreal Bevacizumab (Avastin) on visual acuity and central foveal thickness in patients with vascular retinopathies. Study Design: Quasi experimental study. Place and Duration of Study: Armed Forces Institute of Ophthalmology (AFIO) Rawalpindi, from 1 June 2011 to 31 May 2012. Patients and Methods: Forty four eyes of 36 patients with macular oedema and/or retinal neovascularization due to retinal vascular diseases were included in final analysis. Each patient underwent complete ophthalmic examination including best corrected logMAR visual acuity (logMAR BCVA), slit lamp biomicroscopy, intraocular pressure measurement, and central foveal thickness (CFT) measurement. Intravitreal Bevacizumab (Avastin) was given in a dose of 1.25 mg/ 0.05 ml under topical anesthesia. Primary outcome measures were logMAR BCVA and CFT values on optical coherence tomography (OCT). Secondary outcome measures were IOP at 1st hour after intravitreal Bevacizumab (IVB) and ocular complications of IVB. These study parameters (excluding IOP) were recorded at 2 weeks, 4 weeks, 8 weeks, 12 weeks and 24 weeks after IVB injection. Results: Mean age of the study population was 55.36 ± 14.01 years with 78% male patients. Total of 58 IVB injections were given with sub conjunctival hemorrhage (22%), IOP > 21 mm Hg (28%), corneal erosion (7%) and lens injury (3%) were the main complications. Baseline mean logMAR BCVA was 1.24 ± 0.69 and mean CFT was 486.61 ± 145.29 microns that changed to 0.71 ± 0.65 and 310.98 ± 72.90 microns respectively at 2 weeks after IVB injection. Significant visual improvement and reduction in CFT observed at 2 weeks after IVB remained stable throughout the follow up period. Conclusion: Intravitreal Bevacizumab results in significant visual improvement and reduction in macular oedema in patients with various proliferative retinopathies.